Visualizing Thought: Students’ Critical Thinking Development through Infographic Writing in Project-Based EFL Learning - Ayuni J Burhan; Muhammad Tahir; Andi Asrifan (STIT Buntet Pesantren Cirebon, 2026)
The increasing focus on higher-order thinking and multimodal literacy in modern language education has heightened interest in teaching methods that incorporate critical inquiry, digital communication, and significant writing experiences. Although there is growing interest in infographic-based learning, empirical information elucidating how infographic writing fosters critical thinking growth in secondary English as a Foreign Language classrooms is still scarce, especially in project-based pedagogical contexts. This study examined how infographic writing integrated into Project-Based Learning enhanced students' critical thinking and writing engagement in an Indonesian secondary school setting. The study utilized a convergent mixed-methods design, involving 64 eleventh-grade students and incorporating writing pre- and post-tests, critical thinking rubrics, questionnaires, and semi-structured interviews. Quantitative results indicated significant enhancement in the dimensions of interpretation, analysis, evaluation, inference, explanation, and self-regulation, along with improved organization and coherence in students' writing performance. Qualitative data indicated that infographic development fostered reflective thinking, collaborative problem-solving, information appraisal, and visual-textual meaning construction; nonetheless, students encountered problems associated with vocabulary restrictions and computer literacy. The study conceptualizes infographic writing as a modality of critical thinking practice rather than solely a visual learning exercise. The findings underscore the capacity of project-based multimodal composition to enhance cognitively stimulating and digitally adaptive EFL instruction in secondary education.